Economics of Sesame and Its Use Dynamics in Ethiopia. (30th August 2022) - Sirany, Teshome; Tadele, Esubalew
Abstract : Ethiopia's oilseed industry makes a major contribution to foreign exchange revenues. Ethiopia's three main oilseed crops (sesame, soybean, and Niger seed) account for about 20% of the country's total agricultural export profits, second only to coffee. Even though Ethiopia is one of the world's largest producers and exporters of sesame seeds, the country is facing increasing supply and demand restrictions. This paper begins with an examination of one of the most prominent oil crops in the country. It is a highly adaptable crop that may be used for anything from subsistence to commercial output. We established a comprehensive scientific understanding of the crop using a systematic review of the current literature and deductive logical reasoning that can be used to inform future research and policies. Various exclusion and inclusion criteria were used to filter the most notable findings. Millions of growers and other market participants are employed throughout the oilseed value chain. Reduced sesame productivity, pests and diseases, and limited access to modern technologies are all severe supply-side constraints. On the demand side, traders and market distortion, as well as an artificially higher home price and the ease with which unskilled labor can enter the market, are all factors. Other demand-side constraints include worldwide price volatility, a highly concentrated export market, and intense global competition. Ethiopia's sesame seed development potential is being severely hampered by these restrictions. If farmers, dealers, and the government do not address these issues strategically, the country may soon lose its competitiveness in the global sesame seed market. This will contribute to Ethiopia's ongoing discussion about how to better inform private and public sector policies and investments to increase sesame production, transform agriculture, improve nutrition and food systems, and be able to ease supply- and demand-side restrictions. In a nutshell, an increased area under cultivation combined with best agronomic practices could boost sesame production. Farmers, policymakers, researchers, and other stakeholders must thus intervene to enhance sesame production. Future studies should concentrate on how to boost sesame output in farmers' fields while following appropriate sesame production technology and agronomic principles.